Hospital bed utilisation in the NHS, Kaiser Permanente, and the US Medicare programme: analysis of routine data. Issue 7426 (27th November 2003) - Ham, Chris; York, Nick; Sutch, Steve; Shaw, Rob
Abstract: Objective To compare the utilisation of hospital beds in the NHS in England, Kaiser Permanente in California, and the Medicare programme in the United States and California. Design Analysis of routinely available data from 2000 and 2001 on inpatient admissions, lengths of stay, and bed days in populations aged over 65 for 11 leading causes of use of acute beds. Setting Comparison of NHS data with data from Kaiser Permanente in California and the Medicare programme in California and the United States; interviews with Kaiser Permanente staff and visits to Kaiser facilities. Results Bed day use in the NHS for the 11 leading causes is three and a half times that of Kaiser's standardised rate, almost twice that of the Medicare California's standardised rate, and more than 50% higher than the standardised rate in Medicare in the United States. Kaiser achieves these results through a combination of low admission rates and relatively short stays. The lower use of bed days in Medicare in California compared with Medicare in the United States suggests there is a "California effect" as well as a "Kaiser effect" in hospital utilisation. Conclusion The NHS can learn from Kaiser's integrated approach, the focus on chronic diseases and their effective management, the emphasis placed on self care, the role of intermediate care, and the leadership provided by doctors in developing and supporting this model of care.